Feasibility of Rapid Development and Deployment of a Telemedicine Program in a Foot and Ankle Orthopedic Practice. (March 2021) - Manz, Wesley J.; Goel, Rahul; Fakunle, Omolola P.; Labib, Sameh A.; Bariteau, Jason T.
Background: A lack of access to care is predictably associated with negative outcomes in foot and ankle surgery. Despite recent advances in telecommunication technologies, the field of orthopedics has been slow to adopt these resources in offsetting barriers to care. The COVID-19 pandemic has forced departments to change their clinical approach, lending unprecedented opportunity to better understand how telehealth may bridge this care gap in foot and ankle practices. The purpose of this study was to assess patient-reported outcomes of telemedicine encounters, including comfort and patient satisfaction. Our hypothesis was that patients would be significantly less satisfied with telemedicine when compared with in-office appointments for all nonemergency visit types. Methods: Telemedicine satisfaction was assessed via phone survey with a modified 1 to 5 Likert scale. Patients who had completed a telemedicine visit between April 13, 2020, and June 19, 2020, were eligible to participate. Patient demographics were recorded, and data were analyzed using paired and independent t tests for parametric continuous data and Fisher's exact and chi-square tests for noncontinuous data. A total of 216 patients completed the telemedicine questionnaire. Results: The overall mean satisfaction for telemedicine visits (4.7) was significantly lower than that for in-office visits (4.9) ( P < .001). However, the majority (90.3%) of patients reported they would use telemedicine again in the future. When compared, patients seeking fracture care had significantly higher telemedicine satisfaction (4.9, n = 38) than those receiving nonfracture care (4.6, n = 178) ( P = .001), and those greater than 50 miles from the clinic had higher satisfaction (5.0, n = 14) than patients living within 50 miles of the clinic (4.7, n = 202) ( P < .001). Conclusion: Patients were more satisfied with their in-office clinic visit than telemedicine, although the vast majority of patients endorsed a willingness to utilize telemedicine in the future. Patients with trauma and greater barriers to foot and ankle care were more satisfied with their telemedicine visits. Level of Evidence: Level III, retrospective cohort study.